Case studies of field investigation results on Pulau Sakra - Lim, Kia Wee. (2008)
The aim of this thesis was to present and discuss the field investigation and laboratory analysis results of three plants located on the one of southwestern islands of Singapore, Pulau Sakra, where the petrochemical industry is located. The three plants have been manufacturing plastic products and biochemicals.